Agricultural support policies and GHG emissions from agriculture in Latin America: relationships and policy implications for climate change - Sara A. Wong; Gonzalo Rondinone; Carmine Paolo De Salvo (Revista Iberoamericana de Estudios de Desarrollo)
Domestic support policies for farmers and agriculture, through their price effect, have been deemed potentially environmentally harmful; for example, in developing countries, agricultural prices have been set- below the world market prices, aiming to secure low retail prices for urban consumers. This practice has lowered producer prices, and thereby prevented farmers from adopting ecofriendly production techniques. This study uses policy data —market price support (MPS) and general service support estimates (GSSE) as shares of total support estimate (TSE)— and greenhouse gases (GHG) data for main crops and livestock sectors in 18 Latin-American countries and it applies cluster analysis to construct a typology that highlights patterns between policy incentives for agricultural crops and activities and GHG emissions. The results suggest that an increase in the TSE and/or MPS comprising a large share of the TSE leads to an increase in GHGs. Conversely, GHGs fall when GSSE comprise a larger share of the TSE.